Leituras laplancheanas da obra de Melanie Klein : algumas contribuições para a teoria da constituição psíquica - Marcela Maria dos Santos (2019)
Understanding the importance of the work of Melanie Klein, the present research tried to recover key concepts of its theory, whose final result was construction of two articles. In the first article, castration is investigated in Klein, based on Laplanche’s criticisms of the subject. It concludes that the projective genesis of castration, as described by Klein, corroborates for the Laplancheana thesis of castration as translation code of the sexual. In the second article, the theory of Melanie Klein’s positions, especially the schizoparanoid position, was investigated. At this point, some approximations were made between Jean Laplanche’s theory of generalized seduction and Klein’s constitutional theory. Next, the thesis of Jacqueline Lanouzière, who conceives the process of breastfeeding as a scene originating from seduction, is discussed. The author goes through Klein’s theory, looking for traces of the radicalism of otherness in the psychic constitution. It is concluded that the schizoparanoid organization, described by Klein, is a translation organization of the I to deal with an intrusion caused by the process of generalized seduction that occurs in the adult-baby relationship